2016
DOI: 10.1016/j.str.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Recognition of Eukaryotic Elongation Factor 2 Kinase by Calmodulin

Abstract: SUMMARY Binding of Ca2+-loaded calmodulin (CaM) activates eukaryotic elongation factor 2 kinase (eEF-2K) that phosphorylates eEF-2, its only known cellular target, leading to a decrease in global protein synthesis. Here, using an eEF-2K-derived peptide (eEF-2KCBD) that encodes the region necessary for its CaM-mediated activation, we provide a structural basis for their interaction. The striking feature of this association is the absence of Ca2+ from the CaM C-lobe sites, even under high Ca2+ conditions. eEF-2K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 58 publications
4
50
2
Order By: Relevance
“…Apo-CaM and Ca 2ϩ /CaM Adopt a Common Mode of Binding at the C-lobe to Promote eEF-2K Activity toward eEF-2-We found that saturating apo-CaM induces a maximal eEF-2K activity against Pep-S to within 2-fold of Ca 2ϩ /CaM (Fig. 3F), suggesting that the final active conformations of auto-activated eEF-2K do not discriminate between these two structurally distinct forms of CaM when phosphorylating Pep-S. Our recent structure of the CBD ⅐ Ca 2ϩ -CaM complex (Protein Data Bank code 5J8H) suggests this may be due to a common binding mode of the Ca 2ϩ -loaded and Ca 2ϩ -free forms of CaM, where the CBD engages CaM mainly through the C-lobe, with engagement of the N-lobe (35) only occurring in the presence of Ca 2ϩ , thereby increasing the overall affinity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Apo-CaM and Ca 2ϩ /CaM Adopt a Common Mode of Binding at the C-lobe to Promote eEF-2K Activity toward eEF-2-We found that saturating apo-CaM induces a maximal eEF-2K activity against Pep-S to within 2-fold of Ca 2ϩ /CaM (Fig. 3F), suggesting that the final active conformations of auto-activated eEF-2K do not discriminate between these two structurally distinct forms of CaM when phosphorylating Pep-S. Our recent structure of the CBD ⅐ Ca 2ϩ -CaM complex (Protein Data Bank code 5J8H) suggests this may be due to a common binding mode of the Ca 2ϩ -loaded and Ca 2ϩ -free forms of CaM, where the CBD engages CaM mainly through the C-lobe, with engagement of the N-lobe (35) only occurring in the presence of Ca 2ϩ , thereby increasing the overall affinity.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the S500D/ W85S and S500E/W85S mutants are 10-and 5-fold more active than the W85S single mutant, respectively. Although not definitive, this may reflect our in vitro experiments demonstrating that Ser-500 phosphorylation greatly enhances the ability of CaM to activate eEF-2K, enough so as to partially rescue the activity of eEF-2K W85S, which binds CaM very weakly (35).…”
Section: Autonomous and Non-autonomous Mechanisms Contribute To The Pmentioning
confidence: 88%
See 2 more Smart Citations
“…Both CaM dynamics and motif-dependent target-protein binding have been extensively studied via both experiments [2,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and simulations. Indeed, all-atom molecular dynamics (MD) simulations allow for a detailed description with molecular insights.…”
Section: Introductionmentioning
confidence: 99%